STEROIDAL SAPOGENINS SOURCE FOR CORTICAL STEROIDS - MARKER, RE; APPLEZWEIG, N (HOTEL GENOVA, CD. MEXICO, DF, MEX, 1949)
Effects of cortisone in the treatment of arthritis and its possibilities against cancer have greatly stimulated research to find suitable starting materials for its production.
CHRONOBIOLOGIA
Keywords: STEROIDAL SAPOGENINS, SOURCE, CORTICAL STEROIDS; MULTIDISCIPLINARIA; QUIMICA FISICA; QUIMICA AMBIENTAL